Assessment of genetic diversity of some finger millet accessions using morphological and SSR markers - Kaluthanthri, D.V.S.; Dasanayaka, P.N. (3rd Global Conference on Entomology 2016, 2016)
Attached
Keywords: finger millet; morphological markers; microsatellite; Germplasm; characterization